Free radical damage and its control - Rice-Evans, Catherine; Burdon, R. H. (Roy Hunter) (New comprehensive biochemistry ;, 1994)
This book provides a comprehensive treatise on the chemical and biochemical consequences of damaging free radical reactions, the implications for the pathogenesis of disease and how this might be controlled endogenously and by radical scavenging drugs. Oxidative stress may be influenced by exogenous agents of oxidative stress, radiation, trauma, drug activation, oxygen excess, or by exogenous oxidative stress which is associated with many pathological states including chronic inflammatory disorders, cardiovascular disease, injury to the central nervous system, and connective tissue damage. Thi.